2000
DOI: 10.1159/000017468
|View full text |Cite
|
Sign up to set email alerts
|

Transport of <i>L</i>-Citrulline in Neural Cell Cultures

Abstract: Uptake of L-[14C]citrulline was studied in cell culture models of the main neural cell populations, in astroglia-rich primary cultures derived from neonatal rat brain, in rat glioma cells C6-BU-1, in cells of the murine microglial clone N11 and in the glioma × neuroblastoma hybrid cell line 108CC15 with neuronal properties. For comparison, cells of the peripheral macrophage cell line RAW 264.7 were also investigated. A saturable component of uptake was found in all cases with KM values be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 34 publications
2
13
0
Order By: Relevance
“…There are sodium-independent transporters in the nervous system (26) and sodium-dependent transporters in rat endothelial cells (33). In the kidney, Mitsuoka et al (19) identified B(0)AT1 and b(0,ϩ)AT, sodiumindependent and -dependent transporters of citrulline on the apical membrane of cultured rat renal proximal tubular cells.…”
Section: Discussionmentioning
confidence: 99%
“…There are sodium-independent transporters in the nervous system (26) and sodium-dependent transporters in rat endothelial cells (33). In the kidney, Mitsuoka et al (19) identified B(0)AT1 and b(0,ϩ)AT, sodiumindependent and -dependent transporters of citrulline on the apical membrane of cultured rat renal proximal tubular cells.…”
Section: Discussionmentioning
confidence: 99%
“…Neutral amino acids such as L -citrulline are transported through cell membranes by several distinct transport systems in different cell types, including macrophages [14], rat aortic smooth muscle cells [15], neural cells [16], bovine aortic endothelial cells [17], and intestinal cells [2]. Systems B 0 and B 0,+ , as Na + -dependent transport systems for neutral amino acids, have been identified [18].…”
Section: Introductionmentioning
confidence: 99%
“…In some NOS-containing cells, the intracellular concentration of L-arginine can be well above the K m of NOS. Several mechanisms have been proposed to explain this arginine paradox: the co-localization of arginine transporters and NOS, the intracellular regeneration of arginine from citrulline, a balance between arginase and NOS activity, and the regulation of transport-system mRNA levels by NO concentration (Schmidlin et al 2000;Rasmusen et al 2005).…”
Section: Discussionmentioning
confidence: 99%